Daytime revolution [videorecording (DVD)] - Lennon, John, 1940-1980; Ono, Yōko; Douglas, Mike; Seale, Bobby, 1936-; Nader, Ralph; Carlin, George; Rubin, Jerry; Leggett, Mark, 1954- (Kino Lorber, 2024)
This documentary explores when, in February 1972, John Lennon and Yoko Ono took over The Mike Douglas show for a week, using the popular daytime platform to explore political and social issues. They invited controversial guests, including Yippie founder Jerry Rubin, Black Panther chairman Bobby Seale, activist Ralph Nader, and comedian George Carlin, sparking candid discussions with the audience. Their unconventional approach blended serious political discourse with music and art, challenging the traditional talk show format. This unique television event demonstrated the power of media as a tool for activism and artistic expression.